Deep syntactic tree prediction - Výboch, Peter; Vencovský, Filip; Kliegr, Tomáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
In this work, we will be considering one possible implementation of machine learning algorithm for deep syntactic tree prediction. Specifically, we will rely on a tectogrammaticalrepresentation of a dependency relationships of a tectogrammatical tree and test a reasonablycompact solution of said task.In the introduction, we will discuss a historical context of natural language processing andoutline the motivation for this work. In the next chapter tectogrammatical representationand structure of a tectogrammatical tree will be addressed. Further, we will consider sometheoretical preliminaries for the implementation of the neural networks and for a short timeturn to the specifications of a dataset. Then, we will describe the implementation details ofthe data extracting algorithm, as well as the neural network. We will close-off with assessmentof the results, gathered from the tests.
Vedoucí práce: Filip Vencovský
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses